Pengaruh Kesehatan Mental Terhadap Perilaku Bunuh Diri Pada Remaja Di SMAK X - Yulyanti Minarsih; Yohanes Hans Monteiro; Devi Marganing Tyas; Nur Ainy Sadijah (Departement of Mathematics Education, 2024)
Suicide is a consciouse effort and aims to end life, the individual consciously desires and attempts to realize his desire to die. Adolescence is a transition period from childhood to adulthood. Adolescence is a transtional period where it is often difficult to complete things problem. This difficulty gives rise to suicidal behavior in adolescents. Mental health refers to a good emotional and psychological condition, which allows individuals to use their congnitive and emotional abilities optimally in daily life. The aim pf this research was to determine the influence of mental health on adolenscent suicidal behavior at SMAK X. The research with a two group pretest-posttest design. The total sample for this study was 30 teenagers. The sampling technique is proposive sampling. The statistical test used is the paired samples T Test. There is an influence of mental health on suicidal behavior among teenagers at SMAK X.